Settlement of Khulu Talak Cases or Divorce Claims According to Law Number 16 Of 2019 Concerning Amendment to Act Number 1 Of 1974 Regarding Marriage and Compilation of Islamic Law - Ru’fah Abdullah; Atu Karomah (Ridwan Institute, 2023)
The purpose of the study was to find out the reasons for filing for divorce at the Banjarmasin Religious Court and to find out the legal consequences of divorce on the rights of the wife. Types of empirical legal research or sociological legal research. The research approach uses a statutory approach and a conceptual approach. The results of this study indicate that the reasons that cause a wife to file a divorce petition against her husband at the Banjarmasin Religious Court are due to economic factors, the husband is sentenced to prison, abuse, and infidelity. The reasons for the divorce lawsuit are normative juridical in accordance with Article 19 of Government Regulation Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974 concerning Marriage. The legal consequence of a wife suing for divorce from her husband is that the ex-wife is still entitled to mut'ah and a living based on the Circular Letter of the Supreme Court Number 2 of 2019 and the Regulation of the Supreme Court Number 3 of 2017.